PSMD14 stabilizes estrogen signaling and facilitates breast cancer progression via deubiquitinating ERα - Yang, Penghe; Yang, Xiao; Wang, Dehai; Yang, Huijie; Li, Zhongbo; Zhang, Chenmiao; Zhang, Shuqing; Zhu, Jian; Li, Xin; Su, Peng; Zhuang, Ting (Oncogene, 2024)
The over-activation of ERα signaling is regarded as the major driver for luminal breast cancers, which could be effective controlled via selective estrogen receptor modulators (SERM), such as tamoxifen. The endocrine resistance is still a challenge for breast cancer treatment, while recently studies implicate the post-translational modification on ERα play important roles in endocrine resistance. The stability of ERα protein and ERα transcriptome are subject to a balance between E3 ubiquitin ligases and deubiquitinases. Through deubiquitinases siRNA library screening, we discover PSMD14 as a critical deubiquitinase for ERα signaling and breast cancer progression. PSMD14 could facilitate breast cancer progression through ERα signaling in vitro and in vivo, while pharmaceutical inhibition of PSMD14 via Thiolutin could block the tumorigenesis in breast cancer. In endocrine resistant models, PSMD14 inhibition could de-stabilize the resistant form of ERα (Y537S) and restore tamoxifen sensitivity. Molecular studies reveal that PSMD14 could inhibition K48-linked poly-ubiquitination on ERα, facilitate ERα transcriptome. Interestingly, ChIP assay shows that ERα could bind to the promoter region of PSMD14 and facilitate its gene transcription, which indicates PSMD14 is both the upstream modulator and downstream target for ERα signaling in breast cancer. In general, we identified a novel positive feedback loop between PSMD14 and ERα signaling in breast cancer progression, while blockade of PSMD14 could be a plausible strategy for luminal breast cancer.